Female Intrasexual Competition and Its Link to Menopausal Stage, Sex Hormone Levels, and Personality Characteristics - Fiacco, Serena; Arpagaus, Carla; Mernone, Laura; Ehlert, Ulrike (Frontiers in Global Women's Health, 2021)
Background: Female intrasexual competition (ISC) represents a unique form of social interaction. It describes behaviors primarily applied to enhance a woman's ability to outcompete other women. Previous research suggests that female ISC is influenced by personality characteristics and sex hormones. Although these factors most likely interact to predict female ISC, no previous study has investigated those factors in parallel in order to link theories from social psychology and biology. Women at the end of the reproductive lifespan represent the ideal study population, as they allow for a controlled hormonal environment. Materials and Methods: Healthy pre- (N = 53) and postmenopausal (N = 56) women were classified according to the Stages of Reproductive Aging Workshop (STRAW+10) criteria. In the follicular phase (for premenopausal women) or on a random day (for postmenopausal women), questionnaires were administered to assess the general tendency to compete intrasexually and the tendency to compete on appearance, attention/interpersonal success, and competence. Additionally, personality characteristics (neuroticism, extraversion, openness, agreeableness, conscientiousness, and self-esteem) were assessed. On the same day, each subject provided an 8 a.m. saliva sample for estradiol, testosterone, progesterone, and dehydroepiandrosterone sulfate. T-tests tested for between-group differences and separate multiple linear regression models tested for an effect of continuous hormone levels and personality characteristics on ISC. Further models were run, testing for an interaction with menopausal stage. Results: No group differences in ISC were evident (all p > 0.05). In premenopausal women, estradiol levels positively predicted the competition for attention (β = 2.103, p = 0.022). In postmenopausal women, self-esteem predicted the tendency to compete overall (β = −0.208, p < 0.001), on appearance (β = −0.061, p = 0.01), on competence (β = −0.087, p < 0.001), and on attention/interpersonal success (β = −0.060, p = 0.01). Discussion: These results, though cross-sectional, suggest that women continue to compete intrasexually in postmenopause, giving rise to new questions about the function of female ISC. If confirmed, the findings will indicate that hormones guide competitiveness in fertile women, whereas self-esteem accounts for individual differences in competitiveness post-reproduction. Particularly the function of postmenopausal ISC warrants further investigation.